Next-Generation Sequencing Reveals Novel Homozygous Missense Variant c.934T > C in POLR1C Gene Causing Leukodystrophy and Hypomyelinating Disease - Naseer, Muhammad Imran; Abdulkareem, Angham Abdulrahman; Pushparaj, Peter Natesan; Saharti, Samah; Muthaffar, Osama Y. (Frontiers in Pediatrics, 2022)
Leukodystrophies are a diverse group of genetically established disorders categorized by unusual white matter changes on brain imaging. Hypomyelinating leukodystrophies (HLDs) are a group of neurodevelopmental disorders that affect myelin sheath development in the brain. These disorders are categorized as developmental delay, spasticity, hypotonia, and intellectual disabilities. We describe a patient with developmental delay, cerebellar ataxia, spasticity, hypotonia, and intellectual disability from a healthy family member. Whole exome sequencing (WES) was performed to identify causative variants, which were further analyzed by bioinformatic analysis. WES was performed, and Sanger sequencing-based segregation analysis confirmed the presence of the homozygous missense variants of NM_203290.3 c.934T > C p.Ser312Pro of RNA polymerase I and III subunit C (POLR1C) gene in this patient and heterozygous variant in the unaffected carrier father and mother, supporting the pathogenicity and inheritance pattern of this variant. Furthermore, the variant identified by WES was validated in healthy controls (n = 100) using Sanger sequencing analysis. Finally, our study explained the important use of WES in disease diagnosis and provided further evidence that the variant in the POLR1C gene may play an important role in the development of hypomyelinating leukodystrophy in Saudi families.